2007
DOI: 10.1021/bi7006383
|View full text |Cite
|
Sign up to set email alerts
|

Thermodynamic and Structural Studies of Carbohydrate Binding by the Agrin-G3 Domain

Abstract: Agrin is a key heparan sulfate proteoglycan involved in the development and maintenance of synaptic junctions between nerves and muscles. Agrin's important functions include clustering acetylcholine receptors on the postsynaptic membranes of muscles and binding to the muscle protein α-dystroglycan through its glycan chains. ITC and NMR were used to study the interactions of the Cterminal domain, agrin-G3, with carbohydrates implicated in agrin's functions. Sialic acid caps the glycan chains of α-dystroglycan a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 63 publications
1
3
0
Order By: Relevance
“…ITC measurements for the ligands 9 k, 13 a,b, and 17 a-c were performed at 25 8C using hCD22 d1-3 -Fc [34] (Table 4) and confirmed the behavior typically observed for carbohydrate-lectin interactions, [40][41][42][43] namely an enthalpydriven binding. Less common are entropy-driven carbohydrate-lectin interactions, such as heparin binding to the agrin-G3 domain [42] or the interaction of di-and trisaccharides with calreticulin. [43] The interaction of the parent compound 9 k is dominated by a large enthalpic contribution, which is, however, decreased by substantial entropy costs (Entry 23).…”
Section: Isothermal Titration Calorimetry (Itc)supporting
confidence: 64%
“…ITC measurements for the ligands 9 k, 13 a,b, and 17 a-c were performed at 25 8C using hCD22 d1-3 -Fc [34] (Table 4) and confirmed the behavior typically observed for carbohydrate-lectin interactions, [40][41][42][43] namely an enthalpydriven binding. Less common are entropy-driven carbohydrate-lectin interactions, such as heparin binding to the agrin-G3 domain [42] or the interaction of di-and trisaccharides with calreticulin. [43] The interaction of the parent compound 9 k is dominated by a large enthalpic contribution, which is, however, decreased by substantial entropy costs (Entry 23).…”
Section: Isothermal Titration Calorimetry (Itc)supporting
confidence: 64%
“…In addition, NMR studies have shown that the LG3 domain of agrin binds sialic acid in a Ca 2+ -dependent manner, whilst binding the glycosaminoglycans heparin and heparan sulfate bind independently of Ca 2+ . It remains unclear whether these observations may be relevant for α-dystroglycan binding to agrin (Sallum et al, 2007).…”
Section: Structural Analysis and Modeling Of Different α-Dg Binding Lmentioning
confidence: 99%
“…Precipitates were removed by sedimentation. Pulse-field gradient diffusion experiments (Sallum et al 2007;Whitehead et al 2022) calibrated against the internal standard DSS, gave an Rh of 9.1 ± 0.6 Å for a Zn 2+ -bound 2.4 mM WT sample at 25 o C, pH 6.2, 600 MHz, consistent with a monomeric oligomerization state for the Z7 domain under NMR conditions (Rua et al 2023;Whitehead et al 2022).…”
Section: Nmr Spectroscopymentioning
confidence: 84%
“…Precipitates were removed by sedimentation. Pulse-field gradient diffusion experiments (Sallum et al . 2007; Whitehead et al .…”
Section: Methodsmentioning
confidence: 99%